Control Strategy for Active Vibration Suppression of Flexible Robot Manipulator - Mohd Ashraf, Ahmad; Raja Mohd Taufika, Raja Ismail; Mohd Syakirin, Ramli (2010)

(untitled)
This paper describes the use of angular position control approaches for a flexible robot manipulator with disturbance effect in the dynamic system. A nominal characteristic trajectory following (NCTF) controller is used to actively control the vibration of flexible structures. The controller design, which is comprised of a nominal characteristic trajectory (NCT) and PI compensator, is free from exact modelling and parameter identification. The NCT is determined from an open-loop response and the PI compensator is used to make the manipulator motion to follow the NCT. The effectiveness of the NCTF controller is evaluated and compared with proportional-derivative (PD) controller and fuzzy logic controller as a benchmark. A complete analysis of simulation results for each technique is presented in time domain and frequency domain respectively. Moreover, performances of the controller are examined in terms of vibration suppression and disturbances cancellation.